Current Trends and Future Developments on (Bio- ) Membranes : Microporous Membranes and Membrane Reactors - Basile, Angelo; Ghasemzadeh, Kamran (Elsevier, 2019)
Current Trends and Future Developments on (Bio- ) Membranes: Microporous Membrane and Membrane Reactors focuses on the structure, preparation, characterization and applications of microporous membranes and membrane reactors, including transport mechanisms through a range of microporous membranes. It is a key reference text for R & D managers who are interested in the development of gas separation and water/waste treatment technologies, but is also well-suited for academic researchers and postgraduate students working in the broader area of strategic material production, separation and purification. Users will find comprehensive coverage of current methods, their characterization and properties, and various applications in gas separation and water treatment.